Saving Behavior in Low and Middle-Income Developing Countries : A Comparison - Ogaki, Masao (IMF Working Papers; Working Paper ;, 1995)
The impact of changes in real interest rates on saving and growth is a central issue in development economics. According to one familiar view, a financial liberalization program which increases real interest rates should encourage saving, thereby boosting investment and growth. While such liberalizations have indeed typically succeeded in raising real interest rates, their impact on private saving has been mixed. This paper uses macroeconomic data for a sample of countries with diverse income levels to estimate a model in which the intertemporal elasticity of substitution varies with the level of wealth. The estimated parameters are then used to calculate, in the context of a simple endogenous growth model, the responsiveness of saving to real interest rate changes for countries at differing stages of development.